Our glory and our grief : Torontonians and the Great War - Miller, Ian Hugh Maclean (CEL - Canadian Publishers Collection., 2002)
Our Glory and Our Grief offers a fresh look at the First World War's effect on Canada's second largest city. What happened in Toronto? What did citizens know about the front? How were the enormous sacrifices of the war rationalized?